Educação “em” e “para” empreendedorismo social e solidário: uma análise em IES privadas dos desafios político-pedagógicos - Calderon Arrueta, Lorena de Sousa Ribeiro (Universidade do Vale do Rio dos Sinos, 2024)
This thesis analyses the limits and possibilities of implementing social and solidarity entrepreneurship in Brazilian higher education, especially in private Higher Education Institutions, specially in Business Administration and Technology courses. The focus is on the inclusion of this theme in academic curricula, with a view to meeting social demands and contributing to the promotion of sustainable development. Social and solidarity entrepreneurship is presented as an essential tool for tackling problems such as inequality and social exclusion. The aim was to understand the definitions and theoretical approaches to strengthening the education and practice of social and solidarity entrepreneurship. Understanding the academic community's conceptions and motivations about education and training is crucial to capturing expectations that guide teaching. We sought to characterize and analyze methods of encouraging education for social and solidarity entrepreneurship in higher education, allowing us to identify more effective pedagogical strategies. Also noteworthy is the challenge of describing the political-pedagogical obstacles to implementing a specific curriculum, considering the particularities of the academic environment. The production of subsidies for education in this field would advance the consolidation of the subject in business courses in the Federal District. The research is based on a theoretical-analytical model supported by authors such as França Filho, Gaiger, Hespanha, Laville, Polanyi and Mauss. The concept of entrepreneurship with a cause and the intersection between social and solidarity explore the convergences and specificities of these approaches. The approaches to the solidarity economy, together with the principles of Polanyi and Mauss, offer a theoretical vision of economic practices based on reciprocity and mutuality. Santos' sociology of absences and emergences reveals inclusive alternatives in entrepreneurship, highlighting practices silenced by the dominant economic model. Bourdieu's theories help to understand the dynamics of power and social capital that shape the sector. Plural entrepreneurial education expands training beyond market individualism, while neoliberal rationality is analyzed in terms of its influences on education and entrepreneurship. A qualitative approach was used, and a questionnaire was administered to 286 students in Business Administration and related areas, whose data was processed, tabulated and converted into graphs and tables. Semi-structured interviews were conducted with 24 subjects from the academic world, as well as 11 representatives of the Federal and Regional Administration Councils, whose statements were transcribed and analysed qualitatively. A documentary analysis of the New DCNs for the Undergraduate Degree in Administration was also carried out and interpreted using discourse analysis. The results indicate that the academic community agrees that social and solidarity a path towards a more egalitarian model of economy and society. The majority believe that education on entrepreneurship concepts is fundamental for a humanized education and should be included in academic curricula. Projects and initiatives generated by students have the potential to reduce inequalities and promote ethical business practices, although their implementation faces significant challenges and there is a lot of work ahead to make it happen.
Keywords: Empreendedorismo social e solidário; Educação empreendedora plural; Economia solidária; Impacto social; Social and solidarity entrepreneurship; Plural entrepreneurial education; Solidarity economy; Social impact; ACCNPQ::Ciências Humanas::Sociologia